Energy costs of salt tolerance in crop plants. Issue 3 (11th July 2019) - Munns, Rana; Day, David A.; Fricke, Wieland; Watt, Michelle; Arsova, Borjana; Barkla, Bronwyn J.; Bose, Jayakumar; Byrt, Caitlin S.; Chen, Zhong‐Hua; Foster, Kylie J.; Gilliham, Matthew; Henderson, Sam W.; et al.
Summary: Agriculture is expanding into regions that are affected by salinity. This review considers the energetic costs of salinity tolerance in crop plants and provides a framework for a quantitative assessment of costs. Different sources of energy, and modifications of root system architecture that would maximize water vs ion uptake are addressed. Energy requirements for transport of salt (NaCl) to leaf vacuoles for osmotic adjustment could be small if there are no substantial leaks back across plasma membrane and tonoplast in root and leaf. The coupling ratio of the H + ‐ATPase also is a critical component. One proposed leak, that of Na + influx across the plasma membrane through certain aquaporin channels, might be coupled to water flow, thus conserving energy. For the tonoplast, control of two types of cation channels is required for energy efficiency. Transporters controlling the Na + and Cl − concentrations in mitochondria and chloroplasts are largely unknown and could be a major energy cost. The complexity of the system will require a sophisticated modelling approach to identify critical transporters, apoplastic barriers and root structures. This modelling approach will inform experimentation and allow a quantitative assessment of the energy costs of NaCl tolerance to guide breeding and engineering of molecular components. Abstract : See also the Commentary on this article by Sanders, 225 : 1047–1048 .